Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00259-004-1731-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic features in radiation sensitivity

Abstract: Recent progress especially in the field of gene identification and expression has attracted greater attention to the genetic and epigenetic susceptibility to cancer, possibly enhanced by ionising radiation. This issue is especially important for radiation therapists since hypersensitive patients may suffer from adverse effects in normal tissues following standard radiation therapy, while normally sensitive patients could receive higher doses of radiation, offering a better likelihood of cure for malignant tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 99 publications
0
22
0
5
Order By: Relevance
“…There are many types of DNA damage induced by radiation, such as single-strand breaks (SSBs) and doublestrand breaks (DSBs), sugar and base modifications, and DNA-protein cross-links [3] . The damaged DNA can be not only recognized by the sensory proteins, leading to recruitment of DNA repair enzymes, but also generate signals to delay cell cycle progression until the DNA damage is repaired.…”
Section: Dna Damage and Activation Of Nuclear Sensory Proteinmentioning
confidence: 99%
“…There are many types of DNA damage induced by radiation, such as single-strand breaks (SSBs) and doublestrand breaks (DSBs), sugar and base modifications, and DNA-protein cross-links [3] . The damaged DNA can be not only recognized by the sensory proteins, leading to recruitment of DNA repair enzymes, but also generate signals to delay cell cycle progression until the DNA damage is repaired.…”
Section: Dna Damage and Activation Of Nuclear Sensory Proteinmentioning
confidence: 99%
“…) and BAX to control the cell cycle, DNA repair and apoptosis (3)(4)(5). As a non-DNA injury phenomena, cell membrane disorder and lipid peroxidation have been observed, which induce activation of signal transduction pathways, such as those with protein kinase C (PKC), c-Jun NH 2 -terminal kinase (JNK), ceramide and/or mitogen-activated protein kinase (MAPK) (3).…”
Section: Cip1mentioning
confidence: 99%
“…As a non-DNA injury phenomena, cell membrane disorder and lipid peroxidation have been observed, which induce activation of signal transduction pathways, such as those with protein kinase C (PKC), c-Jun NH 2 -terminal kinase (JNK), ceramide and/or mitogen-activated protein kinase (MAPK) (3). Recent studies have revealed that IR generates reactive oxygen species (ROS) and reactive nitrogen species (RNS) in cells, which leads to DNA injury at random sites as well as the non-DNA injury phenomena (3,6).…”
Section: Cip1mentioning
confidence: 99%
See 1 more Smart Citation
“…This situation of apparently contradictory findings is also characteristic of the low dose radiation field (Nguyen Alternative medicine techniques alter radiation response and Wu, 2011;Kondo, 2011;Nomura, 2011;Zyuzikov, et al 2011). In the latter field however it is now clear that different cell lines, different radiation exposures and even media composition give different results (Bourguignon et al 2005;Ponnaiya et al 1997, Morgan andSowa, 2009;Little, 2010;Dainiak, 2011). This could suggest that these very subtle and sensitive responses are of little relevance in risk assessment.…”
mentioning
confidence: 99%